State of the Art of Geodiversity, Geoconservation, and Geotourism in Costa Rica - Quesada Román, Adolfo (2020)
Over the last decades, Costa Rica became established as a world-leading ecotourism destination due to its environmental policies and environmental awareness. The country is located in a dynamic region where the combination of tectonics and volcanism, and tropical climate and vegetation have molded its landscapes. Our aim is to carry out a review of the geodiversity, geoconservation, and geotourism status in Costa Rica. We analyzed di erent geomorphic environments (volcanic, coastal, karstic, glacial, and fluvial), prospecting the importance of environmental policies and the Conservation Areas National System for the promotion of national geoheritage through geotourism. Our results are critical for the promotion of geosciences to the wider public throughout geotourism and conservation decision-makers. In dynamic, geomorphic, tropical, and developing countries with strong anthropic pressures over their geo- and biodiversity, geoheritage studies might be a priority for increasing their revenues through geotourism and reducing the pressure on their natural resources.